2008
DOI: 10.1111/j.1471-4159.2008.05753.x
|View full text |Cite
|
Sign up to set email alerts
|

A novel reciprocal and biphasic relationship between membrane cholesterol and β‐secretase activity in SH‐SY5Y cells and in human platelets

Abstract: Research into the cause of Alzheimer's disease (AD) has identified strong connections to cholesterol. Cholesterol and cholesterol esters can modulate amyloid precursor protein (APP) processing, thus altering production of the Ab peptides that deposit in cortical amyloid plaques. Processing depends on the encounter between APP and cellular secretases, and is thus subject to the influence of cholesterol-dependent factors including protein trafficking, and distribution between membrane subdomains. We have directl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
27
1

Year Published

2010
2010
2019
2019

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 38 publications
(29 citation statements)
references
References 35 publications
1
27
1
Order By: Relevance
“…Very recently Liu et al have reported that the absolute cholesterol levels may be important for the platelet BACE activity [30]. In the present study we could not detect any significant correlations between circulating cholesterol levels and platelet -or -secretase activity.…”
Section: Discussioncontrasting
confidence: 52%
See 1 more Smart Citation
“…Very recently Liu et al have reported that the absolute cholesterol levels may be important for the platelet BACE activity [30]. In the present study we could not detect any significant correlations between circulating cholesterol levels and platelet -or -secretase activity.…”
Section: Discussioncontrasting
confidence: 52%
“…There was a higher proportion of female subjects in the healthy control group than the MCI or AD groups (Table 1) but there was no significant effect of gender on the platelet secretase activity in any of the groups when tested using Students two tailed t-Test. The patients sampled in this study had a range of MMSE score (15)(16)(17)(18)(19)(20)(21)(22)(23)(24)(25)(26)(27)(28)(29)(30), indicating relative heterogeneity in terms of disease progression (Table 1).…”
Section: Resultsmentioning
confidence: 99%
“…DHA Influences Cholesterol de Novo Synthesis and HMGCR Activity-The effect of cholesterol on degenerative processes in AD is well known. Elevated cholesterol levels are linked to increased amyloid plaque formation in animal models and A␤ aggregation in vitro (52)(53)(54)(55)(56)(57)(58)(59)(60). On the cellular level, cholesterol increases A␤ production by increasing ␤-and ␥-secretase cleavage (44).…”
Section: Dha Increases Nonamyloidogenic Processing and Elevates Sapp␣mentioning
confidence: 99%
“…1 Schematic overview of APP processing and generated cleavage products which reduces A level, decreases cholesterol levels in lipid rafts, where APP is preferentially cleaved by -secretase (Grimm et al 2011c). Investigating -secretase activity in neuroblastoma cells with a broad range of diVerent membrane cholesterol levels revealed membrane cholesterol to signiWcantly inXuence -secretase activity (Liu et al 2009). In return, pharmacological inhibition of -secretase in SH-SY5Y cells leads to increased membrane cholesterol levels (Liu et al 2009).…”
Section: A and Cholesterol Homeostasismentioning
confidence: 97%
“…Investigating -secretase activity in neuroblastoma cells with a broad range of diVerent membrane cholesterol levels revealed membrane cholesterol to signiWcantly inXuence -secretase activity (Liu et al 2009). In return, pharmacological inhibition of -secretase in SH-SY5Y cells leads to increased membrane cholesterol levels (Liu et al 2009). Fibroblasts deWcient in APP and APLP2 or lacking a functional -secretase show an increase in cellular cholesterol levels, which can be reversed by treatment with A 40 .…”
Section: A and Cholesterol Homeostasismentioning
confidence: 98%